2016
DOI: 10.5751/es-08764-210451
|View full text |Cite
|
Sign up to set email alerts
|

Shock events and flood risk management: a media analysis of the institutional long-term effects of flood events in the Netherlands and Poland

Abstract: ABSTRACT. Flood events that have proven to create shock waves in society, which we will call shock events, can open windows of opportunity that allow different actor groups to introduce new ideas. Shock events, however, can also strengthen the status quo. We will take flood events as our object of study. Whereas others focus mainly on the immediate impact and disaster management, we will focus on the long-term impact on and resilience of flood risk governance arrangements. Over the last 25 years, both the Neth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…It became a burning policy issue and showed that the existing flood risk governance was inadequate and insufficiently funded (Kalb and Tak, ). The poor condition of flood defence infrastructure and underinvestment were discussed by the media (Kaufmann et al ., in review) and this had its impact on discourses, and related decisions.…”
Section: Forces Of Stability and Change In Four Dimensions Of Paamentioning
confidence: 97%
“…It became a burning policy issue and showed that the existing flood risk governance was inadequate and insufficiently funded (Kalb and Tak, ). The poor condition of flood defence infrastructure and underinvestment were discussed by the media (Kaufmann et al ., in review) and this had its impact on discourses, and related decisions.…”
Section: Forces Of Stability and Change In Four Dimensions Of Paamentioning
confidence: 97%
“…The implementation of traditional FRM approaches, such as dike reinforcement, is usually rationalized by the urgency of responding immediately to large-scale flood shocks (Kaufmann, Lewandowski, Choryński, & Wiering, 2016) and the consequent political pressure to 'do something' (Zevenbergen, Van Herk, & Rijke, 2017). Fortunately, since 1953, the Netherlands has not been exposed to a major flooding event.…”
Section: Political Dynamics and Power Relationsmentioning
confidence: 99%
“…The professional culture [43] of flood management is traditionally connected to measuring and predicting the behavior of climate, weather, and precipitation as sources of the problem, and the consequential planning and construction of technical flood protection measures as solutions to the problem. Both the definition of the problem and the policies that deal with the problem are disaster driven, meaning that each major flood event creates renewed pressure mostly on policymakers to give rushed real solutions [44,45].…”
Section: Problem Structurementioning
confidence: 99%